Islamic Religious Learning Strategies in Instilling Religious Moderation in the Student Dormitory of Sekolah Tinggi Agama Islam Barus - Dino Saputra; Wakib Kurniawan (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: This study aims to analyze the learning strategy of Islamic religion in instilling the values of religious moderation in the student dormitory of the Sekolah Tinggi Agama Islam Barus, as well as examine the role of musyrif/ah, the form of coaching activities, and the factors that affect the process of internalizing these values. Methodology: This study uses a qualitative approach with a descriptive method. The research subjects consisted of dorm musyrif/ah, students, and dormitory managers. Data collection techniques are carried out through observation, semi-structured interviews, and documentation, while data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawn. Main Findings: The main findings show that Islamic religious learning strategies in instilling the value of religious moderation are carried out through the integration of values in learning materials, dormitory-based character development, dialogical approaches, and examples from supervisors. This strategy has proven to be able to form a relatively moderate understanding and attitude of students' religious beliefs, reflected in the attitude of tolerance, openness, and the ability to interact in a pluralistic environment. However, there are still challenges in the form of conceptual understanding tendencies, the influence of social media, and external environmental dynamics. Novelty/Originality of this study: The novelty of this research lies in the focus of the study that places the dormitory environment as the center of religious moderation learning strategies, which not only emphasizes formal learning in the classroom but also the process of internalizing values through social experiences, habituation, and daily interactions. This research contributes to the development of an integrative and contextual dormitory-based religious development model in shaping the character of moderate students.